Challenges and Strategies of Translating Arabic Novels into English: Evidence from Al-Sanousi’s Fiʾrān Ummī Hissa - Al-Sharif Luma; Al-Abbas Linda (Open Cultural Studies)
This research investigated the strategies adopted to overcome the constraints encountered in the English translation of the Arabic novel Fiʾrān Ummī Hissa in light of Mughazy’s (2016) typology of equivalence and Baker’s (1992) strategies for dealing with idiomatic expressions. The data were collected and categorized thematically into four constraint types: social, political, cultural, and religious. The findings revealed that transliteration was heavily utilized in rendering cultural terms and phrases, such as names, titles, food, and clothing. Paraphrasing was the most used strategy in rendering religious terms requiring clarification, but the extensive details often disrupted the text flow and occasionally led to inaccuracies. Cultural substitution and less expressive words were used in rendering idioms and proverbs, resulting in several mistranslations. In a few cases, omission was applied to terms lacking direct equivalents, yet they were inconsistently reintroduced as transliterated terms in other occurrences. The study recommends that translators follow a consistent translation approach across similar types of cultural expressions to maintain uniformity across the translated text. Translators may use footnotes for terms that require transliteration to help readers understand the cultural context and significance. Further studies could compare similar text translations across languages to explore how cultural contexts influence translation strategies.